1999
DOI: 10.1046/j.1469-8137.1999.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Biotic and abiotic consequences of differences in leaf structure

Abstract: Both within and between species, leaves of plants display wide ranges in structural features. These features include : gross investments of carbon and nitrogen substrates (e.g. leaf mass per unit area) ; stomatal density, distribution between adaxial and abaxial surfaces, and aperture ; internal and external optical scattering structures ; defensive structures, such as trichomes and spines ; and defensive compounds, including UV screens, antifeedants, toxins, and silica abrasives. I offer a synthesis of select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
3
15

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(154 citation statements)
references
References 93 publications
2
131
3
15
Order By: Relevance
“…However, our experiments used the N addition model of Ingestad (1982), and N is provided to the plants in an exponential and progressive manner according to a specific relative growth rate (0.10 and 0.18). At the low N addition rate, the plants are able to adapt to the low N availability (Gutshick 1999). The plants do grow slower, but these are likely able to balance photosynthetic capacity and growth to the available N, and the leaves hardly senesce (Chan-Navarrete et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, our experiments used the N addition model of Ingestad (1982), and N is provided to the plants in an exponential and progressive manner according to a specific relative growth rate (0.10 and 0.18). At the low N addition rate, the plants are able to adapt to the low N availability (Gutshick 1999). The plants do grow slower, but these are likely able to balance photosynthetic capacity and growth to the available N, and the leaves hardly senesce (Chan-Navarrete et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…At their southernmost distribution area, Fagus sylvatica (Bauer et al, 1997) and Abies alba (Rinallo & Gellini 1989) have more sclerophyllous leaves than the central European provenances. The typical Mediterranean conditions enhance sclerophylly, as plants grown in dry environments and under excessive light usually develop greater leaf thickness and mass (Gutschick 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough, Pontes et al (2010) showed that changes in above-ground productivity due to changes in cutting frequency can be explained by traits linked to both tolerance and avoidance mechanisms. The first can be explained, for instance, by the changes in the number of leaves, since a large number of leaves are linked to an increased opportunity for photosynthesis (Gutschick 1999;Franklin and Agren 2002), and the second by the changes in plant stature and palatability. Del-Val and Crawley (2005) has argued that these two mechanisms, i.e.…”
Section: Grass Strategies To Tolerate or Compensate For Cutting/largementioning
confidence: 99%